Limitation of Sovereignty based on International Obligations in a Philosophical Dimension - Yunus, Nur Rohim (ADALAH, 2024)
International law recognizes sovereignty as the right of a state to regulate its own internal affairs. However, this recognition is accompanied by limitations aimed at maintaining world order and respecting human rights. Principles such as non-intervention and respect for territorial boundaries are the foundations of international law that support state sovereignty.